Distraction Modulates Self-Referential Effects in the Processing of Monetary and Social Rewards - Zhu, Jia; Zhan, Youlong (Frontiers in Psychology, 2019)
Reward that is relevant to oneself tends to induce stronger pursuit motivation than reward that links to other people. However, the role of attention in eliciting this “self-referential reward effect” remains unclear. In present two studies, we evaluated the significance of attention in self-referential reward processing utilizing an ownership paradigm, which required participants to complete the visual search task to win monetary rewards (study 1) or social rewards (study 2) for themselves or an acquaintance. Access to attentional resources was manipulated by whether there is a distracted stimulus in the target stimulus. Results of Study 1 revealed that a significant self-referential reward effect emerged under undistracted attention conditions and was associated to better improve in task performances for self-owned monetary rewards. However, distracted attention impaired this self-referential reward effect. Moreover, this impairment of distracted attention was also observed at the self-referential social reward processing in Study 2. These results suggested that distracted attention can impair the pursuit advantage for self-relevant reward because that self-referential processing has a strong dependent for attentional resources.